Factors affecting WoM among telecommunications network users in Indonesia - Ariel Danendra; Fitri Widjaja (Faculty of Business and Economics, University of Surabaya, 2025)
This study aims to analyze the factors influencing WOM (word of mouth) among telecommunications network users in Indonesia. This study has eight dimensions of constructive variables: Service Communication, Quality Service, Relational Value, Trust, Satisfaction, eWOM, fWOM, and Positive Emotional Experience. This study was conducted in a single service setting, and therefore, the results cannot be generalized. Data collected to support the initial variables were distributed to telecommunications network users in Indonesia through 286 Google Forms questionnaire respondents. This investigation used SmartPLS 4 due to its robustness in testing predictive models. This research guides telecommunications service managers in developing and managing user-provider relationship networks. Specifically, this paper shows how business references can be generated and used to build customer retention from various relationship-building strategies. The study shows that service providers who deliver quality services, design superior value, and provide reliable information are better positioned to build strong relationships with customers and, ultimately, to foster Positive Emotional Experiences for both users and providers.